(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Global economic slowdown, credit crunch, and decrease in cross-border loans, trade financing,and FDI all followed the 2008 financial crisis, which had a negative impact on businesses all around theworld. Commercial bankruptcy rules are needed to effectively liquidate and reorganize unviableenterprises and optimize the entire value of proceeds obtained by creditors, owners, workers, or any otherstakeholder. This is why there has been an increase in corporate insolvencies. Credit markets in Indiaare in a distressed situation because to India’s poor insolvency process, considerable inefficiencies, andsystemic exploitation. With a focus on creditor-driven bankruptcy resolution, the Code promisessweeping changes. Early detection and maximization of the value of bankrupt businesses are the goalsof this program. Bilateral and reciprocal agreements with other nations are also part of the Code’sprovisions for dealing with cross-border bankruptcy.